Pengaruh Thrift Shop Dan Dampaknya Terhadap Perekonomian Indonesia - Nur Arifah, Alfin; Ridwan, Rizky; Akbar, Taupik; Muhamad Nur Ihsan, Adi; Nurjanah, Sinta (LP2M Universitas Perjuangan Tasikmalaya, 2024)
This study aims to determine the effect of thrift shop on the indonesian economy. Thrift shop is an activity or method of shopping that aims to save and so that the costs incurred for shopping out are as minimal as possible. The sample of this research was 189 accounting students and data collection used a questionnaire. This method of research uses a quantitative descriptive approach. There are two variables, namely the independent variable (thrift shop) and the dependent variable (indonesian economy). The results showed there was a significant relationship between the thrift shop and the indonesian economy.